Aspergillus sp. isolated in critically ill patients with extracorporeal membrane oxygenation support. (September 2013) - Aubron, Cecile; Pilcher, David; Leong, Tim; Cooper, D. James; Scheinkestel, Carlos; Pellegrino, Vince; Cheng, Allen C.
Abstract This study reports Aspergillus isolation in critically ill patients who underwent extracorporeal membrane oxygenation (ECMO) and highlights the difficulty in establishing a diagnosis of aspergillosis in this population. The diagnosis of Aspergillus infection or colonization was retrospectively performed using the proposed modified criteria of the European Organization for Research and Treatment of Cancer and the Mycoses Study Group (EORTC/MSG) adapted to critically ill patients. Between 2005 and 2011, 11 of 151 patients (7.2%) who underwent ECMO had Aspergillus sp. isolates, 10 in a pulmonary sample and 1 in a mediastinal wound sample. Five patients did not have any classical risk factors for aspergillosis. One patient had a proven invasive pulmonary aspergillosis (IPA), 2 had a putative IPA, and 1 patient had a possible Aspergillus mediastinitis, whilst in 7 patients this was considered colonization. However, the clinical relevance of Aspergillus isolation was based on an algorithm not validated in patients undergoing ECMO. Our data support the need to implement non-invasive diagnostic procedures for aspergillosis in this population.